IL-17a-producing γδT cells and NKG2D signaling mediate bacterial endotoxin-induced neonatal lung injury: implications for bronchopulmonary dysplasia - Cui, Tracy X.; Brady, Alexander E.; Zhang, Ying-Jian; Anderson, Chase; Popova, Antonia P. (Frontiers in Immunology, 2023)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease in preterm birth survivors characterized by inflammation, impaired alveolarization and dysmorphic vasculature. Activated IL-17A+ lymphocytes are key drivers of inflammation in preterm infants. We have shown that in immature mice chronic airway exposure to lipopolysaccharide (LPS) induces pulmonary inflammation, increased IL-17a expression, and hypoalveolarization, a BPD-like phenotype. The source of IL-17a and contribution to lung pathology is unknown. The natural-killer group 2, member D (NKG2D) receptor mediates activation and IL-17a production in γδ T cells by binding to stress molecules. LPS induces NKG2D ligand expression, including Rae-1 and MULT1. We hypothesized that IL-17a+ γδ T cells and NKG2D signaling mediate neonatal LPS-induced lung injury. Immature C57BL/6J (wild type), Nkg2d-/-or Tcrd-/-(lacking γδ T cells) mice were inoculated with 3ug/10ul of LPS from E. coli O26:B6 or 10ul of PBS intranasally on day of life 3, 5, 7, and 10. Selected mice were treated with neutralizing antibodies against IL-17a, or NKG2D intraperitoneally. Lung immune cells were assessed by flow cytometry and gene expression was analyzed by qPCR. Alveolar growth was assessed by lung morphometry. We established that anti-IL-17a antibody treatment attenuated LPS-induced hypoalveolarization. We found that LPS induced the fraction of IL-17a+NKG2D+ γδ T cells, a major source of IL-17a in the neonatal lung. LPS also induced lung mRNA expression of NKG2D, Rae-1, MULT1, and the DNA damage regulator p53. Anti-NKG2D treatment attenuated the effect of LPS on γδ T cell IL-17a expression, immune cell infiltration and hypoalveolarization. LPS-induced hypoalveolarization was also attenuated in Nkg2d-/-and Tcrd-/-mice. In tracheal aspirates of preterm infants IL-17A and its upstream regulator IL-23 were higher in infants who later developed BPD. Also, human ligands of NKG2D, MICA and MICB were present in the aspirates and MICA correlated with median FiO2. Our novel findings demonstrate a central role for activated IL-17a+ γδ T cells and NKG2D signaling in neonatal LPS-induced lung injury. Future studies will determine the role of 3 NKG2D ligands and effectors, other NKG2D+ cells in early-life endotoxin-induced lung injury and inflammation with a long-term goal to understand how inflammation contributes to BPD pathogenesis.